EXPERIMENTAL STUDY ON THE MOTION OF TURBIDITY CLOUDS PRODUCED IN A STAGNANT WATER - IDENO, Hajime; URA, Masaru; AKIYAMA, Juichiro; YING, Xinya; NAKANISHI, Yayoi (PROCEEDINGS OF HYDRAULIC ENGINEERING, 2000)
Motion of turbidity clouds propagating along the bottom boundary, that produced by instantaneous release of turbid water from water surface into a stagnant water, is investigated experimentally. A series of laboratory experiments is conducted by varying inflow condition as well as ambient water depth. The motion of turbidity clouds is found to be distinguishied into two flow regions: the transition and gravity current region. The effects of inflow condition and ambient water depth on the motionof the clouds, and the relationships of the flow characteristics before and after impingement are investigated.